FRI0516 FACTORS ASSOCIATED WITH DECREASED CERVICAL CANCER SCREENING IN WOMEN WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Bruera, S.; Zogala, R.; Lei, X.; Pundole, X.; Zhao, H.; Giordano, S.; Hwang, J.; Suarez-Almazor, M.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that carries an increased risk for both viral illnesses and malignancies, including a greater risk for both human papilloma virus (HPV) infection and cervical cancer. Due to this increased risk, the American Society of Colposcopy and Cervical Pathology guidelines for SLE patients recommend more frequent cervical cancer screening. Few studies have examined patient characteristics associated with decreased cervical cancer screening in patients with autoimmune disease, specifically SLE. Objectives: To estimate cervical cancer screening rates in women with recently diagnosed SLE, and to identify characteristics associated with decreased screening. Methods: We identified women with an initial diagnosis of SLE in the United States MarketScan Commercial Claims and Encounter (CCAE, age 18-64) administrative claims database. We included patients with at least three claims with a lupus diagnosis (first and last at least >90 days apart), no lupus claims within the year before initial claim, and who had been on antimalarial drugs for at least 90 days. We excluded all patients with a previous claim for hysterectomy. Cervical cancer screening was ascertained using diagnosis and procedure codes within 1 year before and 2 years after the first SLE claim. Our covariates included the year of first SLE claim (2001-2014), age at first SLE claim, comorbidity score, insurance type, geographical region, and prescriptions for multiple types of corticosteroids. Control patients included age-matched females without autoimmune disease. Univariate comparison and multivariate logistic regression models were built to evaluate determinants of screening. Results: We included 4, 316 SLE patients (median age 45) and 86, 544 control patients. The screening rate in SLE patients was 73.4% vs 58.5% in the controls (P < 0.001). The screening rate was 71% in 2001, increased to 75% in 2004, then decreased to 70% in 2014 (trend P =0.005). In the multivariate model the following factors were associated with decreased cervical cancer screening: year of first SLE claim 2012-2014 versus 2001-2005 (odds ratio (OR) 0.67, 95% confidence interval (CI) 0.53 – 0.84, P < 0.001); older age 61-64 versus 21-30 (OR 0.27, 95% CI 0.19 – 0.39, P < 0.001); comorbidity score of ≥2 versus <2 (OR 0.71, 95% CI 0.6 – 0.83, P < 0.001); and use of corticosteroids for ≥ 90 days versus <90 days (OR 0.73, 95% CI 0.59 – 0.9, P = 0.003). Insurance type and geographical region were not associated with cervical cancer screening. Conclusion: About three quarters of women with SLE underwent cervical cancer screening within 3 years of their first lupus claim, at higher rates than controls. However, there was a concerning downward trend in screening rates in recent years. In addition, higher risk populations for cervical cancer (older age, increased comorbidities, and longer duration of corticosteroids) had lower screening rates. These findings highlight the need to enhance education for healthcare providers to improve utilization of screening in women with SLE at high risk of cervical cancer. Disclosure of Interests: Sebastian Bruera: None declared, Richard Zogala: None declared, Xiudong Lei: None declared, Xerxes Pundole: None declared, Hui Zhao: None declared, Sharon Giordano: None declared, Jessica Hwang Grant/research support from: MERCK grant funding unrelated to SLE., Maria Suarez-Almazor: None declared